Customers’ Trust on Sustainable Cosmetics Products’ Campaigns - Septiarini, Eka; Tania Adialita (Journal of Trends Economics and Accounting Research, 2024)
The beauty industry in Indonesia is growing rapidly. Along with this growth, some cosmetic industries differentiate by offering the concept of green cosmetics or sustainable beauty. Green campaigns through social media are closely related to the company's strategy to provide knowledge about the environment and inform product values so it will build customer trust and interested to buy sustainable cosmetic products. The objective of this study is to inspect the influence of green campaigns on green trust and green purchase intention of sustainable cosmetics products. This study uses descriptive and associative quantitative methods and analyzed by Smart-PLS Software 3.3. 224 respondents completed the research questionnaire, but only 172 respondents met requirements of this study (had an experience watched green campaigns from sustainable cosmetics). The results showed that the green campaigns affect green trust 65,9% and 54% to the green purchase intention. Green trust affects green purchase intention by 32,2%. Furthermore, green trust also mediates 21,2% the effect of green campaigns on green purchase intention.